THE INFLUENCE OF THIRD PARTY FUNDING AND NON PERFORMING LOANS ON THE DISTRIBUTION OF INVESTMENT CREDIT FOR MSMEs IN AMBON CITY, 2017-2021 - Restia Christianty; Roy Seleky; Hasmia Melati Arifin (SEAN Institute, 2023)
The purpose of this study was to determine whether there is an influence of service quality, facilities and location on visitor satisfaction at the Maimun Palace tourist attraction in Medan. The sample of this research was 78 visitors at Maimun Palace. The method used in this study is quantitative method with multiple linear regression analysis techniques. The data used are secondary data and primary data, hypothesis testing uses the coefficient of determination test (R²), Silmuta